Free contents vs. inconvenience costs: Two faces of online video advertising. (January 2021) - Shon, Minjung; Shin, Jungwoo; Hwang, Junseok; Lee, Daeho
Highlights: It estimates the inconvenience cost of advertisements using a mixed logit model. It performs computer simulations by changing the attributes of advertisements. It identifies the best strategy for online video platform companies. Abstract: With the growth of online video platforms such as YouTube and Netflix, not only the video content market, but also the online video advertising market are growing rapidly. However, as the video content industry expands, the inconvenience caused by video advertisements is increasing, leading to ad-blocking by consumers. To identify the causes of ad-blocking, this study collects consumer preference data using a conjoint survey and estimates the inconvenience cost of advertisements using a mixed logit model. In addition, we performed computational experiments by changing advertising attributes to identify strategies for increasing the market share of online video platform companies. Our results show that the use of personal information affects consumers most seriously, and that platforms can increase market share by reducing the length of advertisements, by reducing the use of personal information, or by blocking all advertising.